2013
DOI: 10.1016/j.bpj.2012.12.005
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Extracellular pH on Selectin Adhesion: Theory and Experiment

Abstract: Selectins mediate circulatory leukocyte trafficking to sites of inflammation and trauma, and the extracellular microenvironments at these sites often become acidic. In this study, we investigated the influence of slightly acidic pH on the binding dynamics of selectins (P-, L-, and E-selectin) to P-selectin glycoprotein ligand-1 (PSGL-1) via computational modeling (molecular dynamics) and experimental rolling assays under shear in vitro. The P-selectin/PSGL-1 binding is strengthened at acidic pH, as evidenced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…Our group has exploited this selectin preference while studying the efficiency of halloysite nanotubes on CTC capture,18,19 where P-selectin was utilized when cells expressed PSGL-1 and E-selectin was used otherwise. We have also found that pathologically decreasing extracellular pH can enhance PSGL-1 binding to P- and L-selectin, while having no effect on E-selectin:PSGL-1 binding 5. Taken together, the use of different selectins can offer another axis of control to more efficiently and selectively capture CTCs.…”
Section: Introductionmentioning
confidence: 65%
“…Our group has exploited this selectin preference while studying the efficiency of halloysite nanotubes on CTC capture,18,19 where P-selectin was utilized when cells expressed PSGL-1 and E-selectin was used otherwise. We have also found that pathologically decreasing extracellular pH can enhance PSGL-1 binding to P- and L-selectin, while having no effect on E-selectin:PSGL-1 binding 5. Taken together, the use of different selectins can offer another axis of control to more efficiently and selectively capture CTCs.…”
Section: Introductionmentioning
confidence: 65%
“…A mastectomy is a surgical procedure characterised by the exeresis of a variable amount of mammary gland tissue, and represents the first choice and the main approach for treating mammary neoplasia. [29] This type of cancer is the third most common in cats, 26 occurring in middle-aged to old animals between 8 and 12 years, and about 90% of neoplasms are malignant. [30][31][32] The mean age of the patients sample (11.1 years old) was within the interval cited by the literature, as well as for the histopathological neoplasm characterisation, considering that all patients of the sample presented a tubular adenocarcinoma which in cats, represents the most frequent type of mammary gland tumors.…”
Section: Discussionmentioning
confidence: 99%
“…All changes in blood pH, in physiological and pathological conditions, occur through variations in three major variables: the CO2, the electrolyte concentrations, and total weak acid concentrations. [26,42] When CO 2 elimination is inadequate relative to the rate of tissue production, will going to increase the H + concentration inducing a decrease in the pH value. [43][44][45][46][47][48][49][50][51][52] pH values below 7.35 are associated with acidaemia, whereas values higher than 7.45 are indicative of alkalaemia (7.4 is considered neutral).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations